(untitled) (Piwulang: Jurnal Pendidikan Bahasa Jawa, 2025)
This study addresses the significant challenge of low student motivation and achievement in cerkak (Javanese short story) writing at SMK Negeri 2 Depok Sleman, where 73.5% of Class XI students failed to meet the Minimum Completeness Criteria (KKM). Utilizing the principles of sociocultural mediation and intrinsic motivation, this Classroom Action Research (CAR), employing the Kemmis and McTaggart model, aimed to enhance students’ writing skills by using music video clips from the popular popdut band, Ndarboy Genk, as an inspiring and culturally relevant medium. The research was structured across pre-cycle, Cycle I, and Cycle II, with data collected from observations and quantitative analysis of student writing products. The findings show a progressive and significant improvement: student mastery increased from 26.47% (average score 68) in the pre-cycle to 67.65% (average score 73) in Cycle I, culminating in 85.29% mastery (average score 78) in Cycle II. The improvement between cycles was attributed to the corrective actions taken, notably enhanced teacher scaffolding focusing on narrative structure, improved time management, and better technical preparation. The cultural and contextual relevance of the Ndarboy Genk media proved highly effective in boosting student engagement, serving as a powerful creative stimulus that facilitated theme development and emotional depth in their narratives. This study concludes that implementing culturally relevant audiovisual media, such as Ndarboy Genk’s video clips, is an effective and innovative pedagogical strategy for significantly improving both the technical skills and engagement in Javanese language writing. It demonstrates the critical role of popular culture in acting as a motivational scaffold within local language education.